2008
DOI: 10.1111/j.1365-2559.2008.03038.x
|View full text |Cite
|
Sign up to set email alerts
|

COX‐2 expression in sporadic colorectal adenomatous polyps is linked to adenoma characteristics

Abstract: This study associates COX-2 epithelial expression with a number of adenoma characteristics that convey an increased risk of malignant transformation. This is in keeping with a positive role for COX-2 in early colorectal carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Our findings of a lack of association of dietary marinederived n23 PUFAs on hyperplastic, as opposed to adenomatous, polyp risk would be expected if the beneficial effects of n23 PUFAs are mediated through a reduction in prostaglandin E 2 . The overexpression of cyclooxygenase-2 has been well documented in adenomatous polyps but has been much less commonly described in hyperplastic polyps, which suggests that prostaglandin E 2 may not play as important a role in hyperplastic polyp development (52)(53)(54).…”
Section: Discussionmentioning
confidence: 98%
“…Our findings of a lack of association of dietary marinederived n23 PUFAs on hyperplastic, as opposed to adenomatous, polyp risk would be expected if the beneficial effects of n23 PUFAs are mediated through a reduction in prostaglandin E 2 . The overexpression of cyclooxygenase-2 has been well documented in adenomatous polyps but has been much less commonly described in hyperplastic polyps, which suggests that prostaglandin E 2 may not play as important a role in hyperplastic polyp development (52)(53)(54).…”
Section: Discussionmentioning
confidence: 98%
“…In models of allergic inflammation and colitis, PGE 2 is well known to have a protective role in limiting inflammation [6165]. This is unlike initiated colon tissue where highly up-regulated COX-2 is known to have tumor-promoting effects [2, 3, 66]. This calls into question whether prevention in normal risk individuals who do not have any defined pathological changes in the colon would benefit from COX-1 or COX-2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of cyclooxygenase-2 (COX-2) and increased PGE 2 synthesis are hallmarks of colon cancer progression [1, 35]. Relatively less is known about the role of other arachidonic acid (AA) metabolites in colon cancer, but they do play a role in the inflammatory response and in carcinogenesis [68].…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism for this difference in NSAID effects is likely related to the differential overexpression of COX-2 seen in adenomatous polyps as opposed to hyperplastic polyps. Although overexpression of COX-2 has been described in hyperplastic polyp specimens,(31) the strength of COX-2 overexpression is less in hyperplastic polyps compared to adenomatous polyps. (32, 33) Kawasaki et al found that 28% of non-serrated adenomas had strong overexpression of COX-2 compared to only 4.2% of hyperplastic polyps.…”
Section: Discussionmentioning
confidence: 99%